José Saramago’s crossover picturebooks and their reception in Turkish - Gökce Vaz de Carvalho, İmren (2021)
ABSTRACT: The article presents a case study of three picturebooks – A Maior Flor do Mundo (2001), El Silencio del Agua (2011), and O Lagarto (2016) – by Portuguese author José Saramago in Turkish translation. It first looks at the implied readers of the books through paratextual analysis, and then assesses the influence of paratextual choices on the responses of real Turkish readers using data culled from social media, online reader platforms and a specially constructed reader group session. The findings demonstrate that the implied crossover reader has disappeared in Turkish, which causes these works to be received as children’s storybooks. This in turn influences real readers’ reactions, depending on who they have bought the books for – children or themselves. KEYWORDS: José Saramago, Crossover Picturebooks, Translation, Reception, Reader Response